Antikroppsstatus mot kattpest hos lejonen i Kolmårdens Djurpark - Ohlson, Karin (SLU/Dept. of Molecular Biosciences, 2006)
The lions at Kolmårdens zoo are vaccinated against Feline Panleukopenivirus (FPV). In 1994 there was an outbreak among the lions at the zoo of FPV disease. A retrospective study has been made to measure the antibodytiters in vaccinated lions and lions that lived during the outbreak. An ImmunoPeroxidase Monolayer Assay (IPMA) was used to analyze the titers in the sera from the lions.